2019
DOI: 10.1002/vjch.201900031
|View full text |Cite
|
Sign up to set email alerts
|

Withanolides from the whole plant of Physalis angulata and their anti‐inflammatory activities

Abstract: From the dichloromethane extract of the whole plant of P. angulata growing in Vietnam, three withanolides including physagulin L (1), physagulin M (2), and withaminimin (3) were isolated by using various chromatography methods. Their chemical structures were determined by detailed analysis of 1D and 2D-NMR data and comparison with reported data. All isolated compounds were tested for their inhibitory activities against NO production in LPS-stimulated RAW 264.7 macrophages. The results showed that compound 3 ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…The structures of the known compounds were identified by spectroscopic methods and comparison with reported data as follows: physagulin K ( 6 ), 28 physagulin A ( 7 ), 29 withaminimin ( 8 ), 18 , 30 physagulin B ( 9 ), 29 physagulin J ( 10 ), 30 (20 S ,22 R )-15α-acetoxy-5α-chloro-6β,14β-dihydroxy-1-oxowitha-2,24-dienolide ( 11 ), 31 physagulin C ( 12 ), 27 and physagulin F ( 13 ). 32 The detailed 1 H and 13 C NMR ( Tables 1 and 2 ) assignments of the one known compound, physagulide I ( 5 ), 33 which have not been reported previously, were made using 1D and 2D NMR techniques ( Tables 1 and 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…The structures of the known compounds were identified by spectroscopic methods and comparison with reported data as follows: physagulin K ( 6 ), 28 physagulin A ( 7 ), 29 withaminimin ( 8 ), 18 , 30 physagulin B ( 9 ), 29 physagulin J ( 10 ), 30 (20 S ,22 R )-15α-acetoxy-5α-chloro-6β,14β-dihydroxy-1-oxowitha-2,24-dienolide ( 11 ), 31 physagulin C ( 12 ), 27 and physagulin F ( 13 ). 32 The detailed 1 H and 13 C NMR ( Tables 1 and 2 ) assignments of the one known compound, physagulide I ( 5 ), 33 which have not been reported previously, were made using 1D and 2D NMR techniques ( Tables 1 and 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…In the last 10 years, there have been four studies using RAW 264.7 cells to determine the anti-inflammatory properties of P. angulata L. and its isolates. Yang et al ( 26 ) isolated physalin E from the stem and aerial parts of P. angulata L. and demonstrated that physalin E significantly reduced TNF-α and IL-6 mRNA and protein expression at 12.5, 25.0 and 50.0 M ( 26 , 27 ). In addition, withaminimin, obtained from dichloromethane extract of the whole plant of P. angulata L., educed nitric oxide (NO) generation in RAW 264.7 macrophages stimulated with lipopolysaccharide (LPS) ( 27 ).…”
Section: Anti-inflammatory Propertiesmentioning
confidence: 99%
“…Yang et al ( 26 ) isolated physalin E from the stem and aerial parts of P. angulata L. and demonstrated that physalin E significantly reduced TNF-α and IL-6 mRNA and protein expression at 12.5, 25.0 and 50.0 M ( 26 , 27 ). In addition, withaminimin, obtained from dichloromethane extract of the whole plant of P. angulata L., educed nitric oxide (NO) generation in RAW 264.7 macrophages stimulated with lipopolysaccharide (LPS) ( 27 ). Using NO production measurements following 1 lg/ml of LPS stimulation, the NO inhibition of each of the isolated compounds was assessed in RAW 246.7 cells.…”
Section: Anti-inflammatory Propertiesmentioning
confidence: 99%
See 1 more Smart Citation